Correlation between Wage Perception with Poultrymen’s Working Motivation on Rural Broiler Farms in Tempel District, Yogyakarta, Indonesia - Andarwati, Siti (Indonesian Society of Animal Science in collaboration with Indonesian Ministry of Agriculture and Faculty of Animal Science UGM, 2014)
This study aimed to analyzed: 1) The amount of wages received by poultrymen and how the system of wages payment, 2) Perception of poultrymen towards wages, 3) Poultrymen's working motivation, and 4) The relationship between perceptions of wage with the poultrymen’s working motivation on rural broiler farms in Tempel District. This research was conducted in Tempel District and involved 30 respondents from different broiler farms. Respondents were elected by purposive sampling method. The methods that used to calculate the wages by farmers were different but had a similar form. Overall average of wages that poultrymen received on one period from rural broiler farm in Tempel District was IDR 2,253,867. Poultrymen perception on wage was high rank with 93% of them had high perception of wage. Working motivation was also high with 80% of poultrymen had high motivation. The result of correlation between wage perception and poultrymen’s working motivation showed didn’t has correlation in both.